2016
DOI: 10.1088/1367-2630/18/7/073036
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamonds carrying silicon-vacancy quantum emitters with almost lifetime-limited linewidths

Abstract: Colour centres in nanodiamonds are an important resource for applications in quantum sensing, biological imaging, and quantum optics. Here we report unprecedented narrow optical transitions for individual colour centres in nanodiamonds smaller than 200 nm. This demonstration has been achieved using the negatively charged silicon vacancy centre, which has recently received considerable attention due to its superb optical properties in bulk diamond. We have measured an ensemble of silicon-vacancy centres across … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 27 publications
4
73
0
Order By: Relevance
“…One advantage of possessing inversion symmetry is the guarantee of vanishing of permanent electric‐dipole moment, which leaves split‐vacancy centers insensitive to the first‐order Stark shift caused by the local electric‐field fluctuations in the environment . Lack of susceptibilities helps mitigate the spectral diffusion experienced by the system, allowing for the observation of nearly lifetime‐limited linewidth as reported by multiple groups, and the realization of transform‐limited linewidth on SiV − , GeV − , and SnV − color centers. Moreover, narrow inhomogeneous distribution of ZPL energy of SiV − centers hosted in bulk diamond enables the direct observation of two‐photon interference (with indistinguishability of 72%) between two distinct SiV − emitters without frequency tuning, an essential step toward on‐demand indistinguishable single‐photon sources featuring high brightness and long‐term stability as required by quantum key distribution and quantum optics applications …”
Section: Optical Properties Of Xv− Color Centers In Diamondmentioning
confidence: 99%
“…One advantage of possessing inversion symmetry is the guarantee of vanishing of permanent electric‐dipole moment, which leaves split‐vacancy centers insensitive to the first‐order Stark shift caused by the local electric‐field fluctuations in the environment . Lack of susceptibilities helps mitigate the spectral diffusion experienced by the system, allowing for the observation of nearly lifetime‐limited linewidth as reported by multiple groups, and the realization of transform‐limited linewidth on SiV − , GeV − , and SnV − color centers. Moreover, narrow inhomogeneous distribution of ZPL energy of SiV − centers hosted in bulk diamond enables the direct observation of two‐photon interference (with indistinguishability of 72%) between two distinct SiV − emitters without frequency tuning, an essential step toward on‐demand indistinguishable single‐photon sources featuring high brightness and long‐term stability as required by quantum key distribution and quantum optics applications …”
Section: Optical Properties Of Xv− Color Centers In Diamondmentioning
confidence: 99%
“…This can be achieved by either cooling the samples below 1 K or by manipulating the phononic environment of the centre using phononic nanostructures16. The rapid development of nanofabrication1718 and growth techniques19 potentially allows for the fabrication of diamond based phononic band gap materials20 or small nanodiamonds to suppress ground state thermalization. As a result, coherence times in the millisecond range seem feasible as the pure spin relaxation time has been determined to be =2.4 ms (ref.…”
mentioning
confidence: 99%
“…This band is mainly due to a zero-phonon line from luminescence of negatively charged (Si-V) -defects, content of which in diamond was found to grow with the increase of concentration of C 12 H 36 Si 5 compound in the mixture. The follow up studies [20] of optical properties of HPHT synthesized Si-doped nanodiamonds have revealed an unprecedented narrow optical transitions for individ- These results indicate the high crystalline quality achieved in these nanodiamond samples, and advance the applicability of nanodiamond-hosted colour centres for quantum optics applications.…”
Section: Hpht Synthesis Of Doped Diamondmentioning
confidence: 79%